THE MATERIAL FLOW: A study in an agricultural equipment manufacturer - Vassoleri, Gabriel Costa; Ribeiro de Campos, Ronaldo (Revista Interface Tecnológica, 2024)
The study focus on a flow of materials in a agricultural implements manufacturer, it uses a descriptve approching to analisses the process of moving materials into alternative rotes. The main point was investigate the situation of this delivery materials rote in currently existing difficulties terms and the proposes of improvements. Through the Consulting of documents wich registers the operations of movimentation of materials flows and the author experiences as a member hired by the company, the mains results apoint to a type of fisic layout wich has limiting factors as well as related difficulties encountered with the description taken during the bibliographic researching phase wich presentes the fisic layout as a important point. Some sugetions were also submitted for improvements to the identified challenges.
Keywords: Internal Logistics; Physical Layout; Agribusiness